Beginning Database-Driven Application Development in Java EE - Vasiliev, Yuli (Apress, 2012)
Beginning Database-Driven Application Development in Java EE:Using GlassFish is an example-driven, practical book that explains in detail how to develop Java EE applications utilizing relational database technologies with examples using Oracle and MySQL as well as the GlassFish application development framework and deployment platform—all based on Java EE. The book brings together the most useful Java EE technologies such as EJB, JPA, and JSF, providing information that can be immediately put to work. Over the course of this book, you will be guided through every step of building and deploying a data-centric Java EE application. As you work through the book-length case study, you will learn how to develop each tier of a Java EE application, including the database tier, persistence tier, business logic tier, and presentation tier.